2013
DOI: 10.1111/bjet.12086
|View full text |Cite
|
Sign up to set email alerts
|

ICT‐supported learning for inclusion of people with special needs: Review of seven educational technology journals, 1970–2011

Abstract: She teaches instructional design and educational technology, learning environments, information and communication technology (ICT)-assisted learning for people with special needs, ICT in health, media education and contemporary learning theories. She is conducting research at all levels of education, adult education, workplace learning, professional development and teacher education. Andreja's website has details of her activities and publications: http://andreja-istenic-starcic.eu/. Spela Bagon is a PhD stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 116 publications
(255 reference statements)
1
43
0
6
Order By: Relevance
“…Ahora bien, si nos situamos en el ámbito de la discapacidad, podemos comprobar que son escasos los estudios que ponen especial énfasis en el potencial que tienen las TIC en estudiantes con diversidad funcional por discapacidad (Shih, Shih, y Luo, 2011;Wallace y Georgina, 2014;Khetarpal, 2014;Istenic y Bagon, 2014;Ramos y Andrade, 2016;Turner-Cmuchal y Aitken, 2016;Alper y Goggin, 2017).…”
Section: Establecimiento Del Problema Y Justificación Del Estudiounclassified
“…Ahora bien, si nos situamos en el ámbito de la discapacidad, podemos comprobar que son escasos los estudios que ponen especial énfasis en el potencial que tienen las TIC en estudiantes con diversidad funcional por discapacidad (Shih, Shih, y Luo, 2011;Wallace y Georgina, 2014;Khetarpal, 2014;Istenic y Bagon, 2014;Ramos y Andrade, 2016;Turner-Cmuchal y Aitken, 2016;Alper y Goggin, 2017).…”
Section: Establecimiento Del Problema Y Justificación Del Estudiounclassified
“…An important aspect that should be considered in inclusive education is the characteristics of students with different SN and the factors requirements that affect their ICT use. Therefore, special attention is required when choosing the appropriate ICT tools to support the learning of different groups of stu-dents with SN [23], as certain particularities can directly affect the ICT use (e.g., poor vision, hearing, language understanding).…”
mentioning
confidence: 99%
“…() concluded that teachers posited that ICT courses were not offered at schools of hearing‐impaired students due to inadequate computer equipment and busy time tables although students had skills and knowledge. In a content analysis of all papers published from 1970 to 2011, Istenic Starcic and Bagon () concluded that early research about inclusion have focused on access to technological equipment and web access at schools to promote inclusion. Schools facilitated the teachers’ use of information technology for classroom preparation for students with special needs.…”
Section: Discussionmentioning
confidence: 99%
“…The topic of ICT for individuals with disabilities has not had considerable attention in the literature (Istenic Starcic and Bagon, ). Research related to special education teachers’ perceptions or attitudes towards using technology, or even special education teachers’ use of technology, in Oman is scarce.…”
Section: Introductionmentioning
confidence: 99%